Educação das relações étnico-raciais para crianças: reflexões a respeito de uma mídia musical - Ferreira, Caroline Camargo (Universidade Federal de São Carlos, 2024)
This work addresses the education of ethnic-racial relations in practice with children, reflecting on some children's media by analyzing the musical project "A Galinha Pintadinha." The exploratory research, conducted as an Undergraduate Thesis in Education at the Federal University of São Carlos, Sorocaba campus, aimed to understand the relationships between music, early childhood education, and the education of ethnic-racial relations, using a qualitative methodology: observing, analyzing, and categorizing through the audiovisual media of YouTube, focusing on music videos that use traditional children's songs. As a result, it can be stated that there is still much to review regarding the presentation of these songs in terms of words and imagery when it comes to affirmative actions for the education of ethnic-racial relations.
Education of ethnic-racial relations for children: reflections on musical media
Keywords: Educação infantil; Educação das Relações Étnico-raciais; Mídias Infantis; Early Childhood Education; Ethnic-Racial Relations Education; Children's Media; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO